2018
DOI: 10.1016/j.jmig.2017.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Successful Laparoscopic Treatment of Chylous Ascites after Pelvic Lymphadenectomy: A Case Report and Peanut Oil Application

Abstract: A 23-year-old female patient with refractory chylous ascites was successfully treated with laparoscopic ligation of the ruptured lymphatic vessel. The young patient developed abdominal distention after right-side pelvic lymph node dissection for dysgerminoma of the right ovary. Conservative managements failed to control the symptoms. Laparoscopic surgery was performed after oral administration of peanut oil, revealing the presence of a whitish fluid in the abdominal cavity. The responsible lesion of the chylou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“… No. Author/year Age/sex Comorbidities Disease/stage Operation/operation time/blood loss Complication (other than chylous ascites) Conservative therapy Method of surgical repair for cylous ascites The days from surgical repair to cure 1 Lee et al [ 23 ]/2019 66/M None Sigmoid colon cancer/I Laparoscopic anterior resection/110 min/10 ml None Octreotide, MCTD, TPN Suture 14 2 Shimajiri et al [ 24 ]/2018 31/M None Neuroendocrine carcinoma/not mentioned Laparoscopic descending colectomy/not mentioned/not mentioned None Octreotide, MCTD, TPN Surgery with fibrin glue 10 3 Won Ha et al [ 25 ]/2015 65/M None Sigmoid colon cancer/IIIB Laparoscopic anterior resection/not mentioned/not mentioned None MCTD, TPN Suture 10 4 Fukui et al [ 26 ]/2017 53/M None Rectosigmoid cancer/not mentioned Laparoscopic low anterior resection/not mentioned/not mentioned None MCTD, TPN Surgery with fibrin glue 14 5 Powell et al [ 27 ]/2012 41/M None Gastro-esophageal reflux disease/not mentioned Laparoscopic Nissen fundoplication/not mentioned/not mentioned None MCTD Suture 6 6 Liu et al [ 28 ]/2017 23/F None Dysgerminoma of the ovary/not mentioned Laparoscopic right side pelvic lymph node dissection/not mentioned/not mentioned None Octreotide, MCTD, TPN Suture 182 …”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… No. Author/year Age/sex Comorbidities Disease/stage Operation/operation time/blood loss Complication (other than chylous ascites) Conservative therapy Method of surgical repair for cylous ascites The days from surgical repair to cure 1 Lee et al [ 23 ]/2019 66/M None Sigmoid colon cancer/I Laparoscopic anterior resection/110 min/10 ml None Octreotide, MCTD, TPN Suture 14 2 Shimajiri et al [ 24 ]/2018 31/M None Neuroendocrine carcinoma/not mentioned Laparoscopic descending colectomy/not mentioned/not mentioned None Octreotide, MCTD, TPN Surgery with fibrin glue 10 3 Won Ha et al [ 25 ]/2015 65/M None Sigmoid colon cancer/IIIB Laparoscopic anterior resection/not mentioned/not mentioned None MCTD, TPN Suture 10 4 Fukui et al [ 26 ]/2017 53/M None Rectosigmoid cancer/not mentioned Laparoscopic low anterior resection/not mentioned/not mentioned None MCTD, TPN Surgery with fibrin glue 14 5 Powell et al [ 27 ]/2012 41/M None Gastro-esophageal reflux disease/not mentioned Laparoscopic Nissen fundoplication/not mentioned/not mentioned None MCTD Suture 6 6 Liu et al [ 28 ]/2017 23/F None Dysgerminoma of the ovary/not mentioned Laparoscopic right side pelvic lymph node dissection/not mentioned/not mentioned None Octreotide, MCTD, TPN Suture 182 …”
Section: Clinical Discussionmentioning
confidence: 99%
“…Surgical repair was performed in six cases, and LL was not carried out in any case. Among these, suturing was performed in four cases, while in two cases, surgery was done with glue [ [23] , [24] , [25] , [26] , [27] , [28] ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…But, because the patient did not respond to the treatment, they treated the patient with five cycles of retroperitoneal radiotherapy. Liu et al [ 17 ] reported a case of a refractory chylous ascites after pelvic lymphadenectomy, wherein they successfully performed laparoscopic ligation of the leaking lymphatics.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Conservative treatments, including fat-free diet, parenteral nutrition, and drainage, are partially effective with prolonged hospital stay but less efficient in those refractory cases. Several successful surgeries have been reported, 5 , 6 but surgical treatment is still controversial with demands for surgical technical at a high level and difficulties in identifying leakage sites at re-operated fields. Consequently, optimal treatments towards lymphatic leakage are still in need.…”
Section: Introductionmentioning
confidence: 99%